2017
DOI: 10.1016/j.foodcont.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the diversity and safety of the predominant Bacillus pumilus sensu lato and other Bacillus species involved in the alkaline fermentation of cassava leaves for the production of Ntoba Mbodi

Abstract: Investigation of the diversity and safety of the predominant Bacillus pumilus sensu lato and other Bacillus species involved in the alkaline fermentation of cassava leaves for the production of Ntoba Mbodi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…This study set out to assess the variability in the bacterial populations across samples of Ntoba mbodi and the potential enzyme activities associated with the predominant strains isolated from Ntoba mbodi. Consistent with previous studies (Ouoba et al, 2010;Vouidibio-Mbozo et al, 2017), we showed that Ntoba mbodi contains high density of bacteria that varied with xylanase;…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study set out to assess the variability in the bacterial populations across samples of Ntoba mbodi and the potential enzyme activities associated with the predominant strains isolated from Ntoba mbodi. Consistent with previous studies (Ouoba et al, 2010;Vouidibio-Mbozo et al, 2017), we showed that Ntoba mbodi contains high density of bacteria that varied with xylanase;…”
Section: Discussionsupporting
confidence: 93%
“…C-32, Bacillus sp.01105, Bacillus altitudinis strain SH156 and Bacillus aerophilus strain JF11. The presence of Bacillus related species is in agreement with previous studies in Ntoba mbodi (Louembe et al, 2003;Vouidibio-Mbozo et al, 2017) and in other alkaline food fermentation products (Steinkraus, 2002;Parkouda et al, 2009;Tamang et al, 2016). Comparison at species level revealed that the Bacillus related species previously reported in Ntoba mbodi, including B. subtilis, B. amyloliquefaciens, B. megaterium, B. macerans, B. cereus, B. polymixa, B. brevis and B. pumilus (Louembe et al, 2003;Kobawila et al, 2005), B. safensis, B. siamensis and Lysinibacillus louembei (Ouoba et al, 2015; Vouidibio Mbozo et al, 2017), were not found at the highest dilution of inoculum (Ntoba mbodi).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Therefore these isolates have been called Bacillus Sp. The presence of the genus Bacillus in food is not surprising, since several studies have reported their presence although most studies have been carried out on fermented foods, it is the case de du NtobaMbodi in Congo Brazzaville [21,26,27], Ugba in Nigeria [28] for is quoted only that.…”
Section: Discussionmentioning
confidence: 99%